A PRODUÇÃO ARTESANAL EM FIBRA DE BURITI: uma análise da qualidade de vida de artesãs ludovicenses - AROUCHE, Katyuscia Karla Mendes (2020)
The study of Quality of Life (QOL) expresses itself as a complex area of knowledge and in growing discussion, since it includes in its agenda the health theme that can be discussed with other knowledge, such as biological, psychological, political, economic, etc. The different fields of knowledge that make up the study of QoL allowed a dialogue with the universe of work, being of interest for the investigation of this research the craft work. Under the objective of analyzing the quality of life from the work of the buriti fiber artisan in the city of São Luís-MA and the repercussions on her health, this exploratory study, through a quali- quanti analysis, described the process of artisanal work in different stages and identified through the observation in the field the presence of workloads, of the physical, chemical, physiological and psychic type and wear processes during its performance by the investigated artisans. Regarding quality of life, the domains included in the WHOQOL-Bref methodological instrument were defined, with adaptation to the scenario of this research. The quality of life for those surveyed presents different interpretations based on their social representations, values and beliefs. It is concluded that the psychological domain and social relations reflect a good quality of life for the researched ones, whereas the physical and environmental domains are compromised in relation to the quality of life of the artisans. In view of this proposal, artisanal work should be considered through discussions of strategies that promote quality of life in this environment, as it is a way of knowing how to add personal, cultural and social benefits.